(untitled) (SCIÉNDO INGENIUM, 2021)
The objective of this research was to obtain reducing sugars from a consortium of Amazonian microalgae, grown in wastewater. The microalgae consortium was cultivated in wastewater for 30 days, in a closed photobioreactor of 7 L capacity at room temperature, 2x36 watt Led lighting, 12-hour light / dark photoperiod and stirring-aeration, measuring the biomass concentration. by optical density at 680 nm every three days, harvested by decantation - centrifugation, to obtain a total biomass of 25.2 gr. The cellular rupture of the dry biomass of the microalgae was carried out by acid hydrolysis at 2, 4 and 6% of sulfuric acid (H2SO4), autoclaved at 120 ° C for 30, 60 and 90 min, the content of reducing sugars in the different Treatments were carried out using the 3,5-dinitrosalicylic acid (DNS) reagent method at 540 nm, obtaining the best yield in reducing sugars (1,406mg / L) for a hydrolysis of 6% of H2SO4 and a time of 90 minutes. Microalgae grown in wastewater, as raw material, are emerging as the most suitable source due to their rapid growth and high content of reducing sugars.